High-Permittivity Polymer–Matrix Composites for the Development of Triboelectric Nanogenerators (TENGs) with Enhanced Performance: A Review - (:unkn) unknown (Springer Nature Switzerland, 2024)
In recent years, the rapid increase in low-power electronics has shifted research focus towards new energy-harvesting devices. Triboelectric energy-harvesting technologies, such as triboelectric nanogenerators (TENGs), offer an efficient way to convert m...
Keywords: Nanogeneradores triboeléctricos; Materiales compuestos